2016
DOI: 10.5935/1678-9741.20160047
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Abdominal Aneurysm Repair in Women: What are the Differences Between the Genders?

Abstract: INTRODUCTION:Abdominal aortic aneurysm has a lower incidence in the female population, but a higher complication rate. It was been hypothesized that some anatomical differences of abdominal aortic aneurysm in women could be responsible for that. We proposed to analyze our data to understand the differences in the clinical and anatomical characteristics and the outcomes of patients undergoing endovascular aneurysm repair, according to gender.METHODS:A retrospective analysis of patients undergoing endovascular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In total, 3392 publications were retrieved from the initial systematic literature search (Supplementary Table I, online only) and 21 publications were obtained by the manually computer-aided bibliographic search from the earlier review. After removing duplicates, screening titles/abstracts and reviewing full-texts, 32 studies met the selection criteria and were included in this meta-analysis, 7,8,[13][14][15][16][17][18][19][20][21][22][23][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] three studies of which were verified by obtaining data through contact with the authors. 29,32,36 Four studies reported independent data for both intact AAA and ruptured AAA, which were separated into two different cohorts.…”
Section: Study Selection and Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 3392 publications were retrieved from the initial systematic literature search (Supplementary Table I, online only) and 21 publications were obtained by the manually computer-aided bibliographic search from the earlier review. After removing duplicates, screening titles/abstracts and reviewing full-texts, 32 studies met the selection criteria and were included in this meta-analysis, 7,8,[13][14][15][16][17][18][19][20][21][22][23][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] three studies of which were verified by obtaining data through contact with the authors. 29,32,36 Four studies reported independent data for both intact AAA and ruptured AAA, which were separated into two different cohorts.…”
Section: Study Selection and Description Of Included Studiesmentioning
confidence: 99%
“…29,32,36 Four studies reported independent data for both intact AAA and ruptured AAA, which were separated into two different cohorts. 30,33,35,39 Finally, we analyzed a total of 36 cohorts (Fig 1), in which 25 cohorts investigated intact AAA, 7,8,[13][14][15][16][17][18][20][21][22][23][28][29][30][31][33][34][35][39][40][41][42]44,45 7 investigated ruptured AAA, 19,30,32,33,35,36,39 and 4 investigated indeterminate AAA. 37,38,43,46 All cohorts were from retrospective studies without high risk bias assessed by Newcastle-Ottawa Scale (Supplementary Table II, online only), 13 cohorts of which were multiple-center studies.…”
Section: Study Selection and Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…(60) It has been reported that women have more complex aneurysms with unfavourable neck anatomy than men, which is reflected in the observation that women are less often eligible for EVAR. (7,41,61) Compared with men, women have higher perioperative mortality after complex EVAR, but not after complex OSR. (60) The impact of a potentially more hostile aneurysm neck morphology in women on mortality could not be accounted for and this limits the interpretation of the role of comorbidity in the mortality disparity.…”
Section: Limitationsmentioning
confidence: 99%
“…7 Indeed, although female patients undergoing EVAR tend to be older, they are also healthier, having fewer diagnosed instances of heart disease, diabetes, concurrent smoking, chronic obstructive pulmonary disease (COPD), and chronic renal dysfunction. 8 There have been several studies where controlling for age, urgency at presentation, comorbidities, and risk factors has resulted in equipoise of perioperative and 1-year mortality. 6 There is interplay between a patient's comorbidities and their aneurysm anatomy, which ultimately determines long-term outcome: successful aneurysm exclusion, prevention of rupture, aneurysm-related mortality, and overall survival.…”
mentioning
confidence: 99%